Dead aid : why aid is not working and how there is another way for Africa - Moyo, Dambisa (Vancouver : Douglas & McIntyre, 2009)
The book reveals why millions are actually poorer because of aid, unable to escape corruption and reduced, in the West's eyes, to a childlike state of beggary. The author uses hard evidence to illustrate that with access to capital and with the right policies, even the poorest nations can turn themselves around.
Includes bibliographical references (p. [164]-180) and index.
rpm 01/06/13
Loans
Keywords: Economic assistance -- Africa; Poor -- Africa; Africa -- Economic conditions -- 21st century; Economic development -- Africa; Investments, Chinese -- Africa; Poverty -- Africa -- Prevention